HUBUNGAN TINGKAT PENDIDIKAN ORANG TUA DENGAN BENTUK KEKERASAN TERHADAP ANAK - Devi Risma; Yeni Solfiah; Defni Satria (Jurnal Educhild : Pendidikan dan Sosial, 2018)
Parents occupy a very important position in child development. Aside from being an educator,parents also act as child protectors from other forms of violence. However, in reality parentssometimes become perpetrators of child abuse with a reason to discipline. This study aims todetermine the relationship between the level of education of parents about children with forms ofviolence against children. The research method is a correlation with the location of research inthree cities in Riau Province. The location of the study was conducted in Bengkalis Regency,Indragiri Hilir Regency and Pekanbaru City. The technique of determining the location of the studyusing a multi stage cluster. The sampling technique with quota random sampling with a total of300 people. The level of education of parents is grouped through the latest education, rangingfrom elementary schools, junior high schools, high schools and universities. The results of thisstudy there is a very significant relationship between the level of education of parents with formsof violence against children. With an F value of 0.348 and a probability of sig 0.00 means thatthere is a significant relationship between the level of education of parents with forms of violencein children. pendidik, orang tua juga berperan sebagai pelindung anak dari bentuk-bentuk kekerasan. Namun,kenyataannya orang tua terkadang menjadi pelaku kekerasan pada anak dengan alasan untukmendisiplinkan. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pendidikan orangtua tentang anak dengan bentuk kekerasan terhadap anak. Metode penelitian merupakan korelasidengan lokasi penelitian di tiga kota di Provinsi Riau. Lokasi penelitian dilakukan di KabupatenBengkalis, Kabupaten Indragiri Hilir dan Kota Pekanbaru. Teknik penentuan lokasi penelitianmenggunakan multi stage cluster. Teknik pengambilan sampel dengan quota random samplingdengan jumlah 300 orang. Tingkat pendidikan orang tua dikelompokkan melalui pendidikanterakhir, mulai dari Sekolah Dasar, Sekolah Menengah Pertama, Sekolah Menengah Atas danPerguruan Tinggi. Adapun hasil dari penelitian ini terdapat hubungan yang sangat signifikanantara tingkat pendidikan orang tua dengan bentuk kekerasan terhadap anak. Dengan nilai F0,348 dan probabilitas sig 0,00 artinya terdapat hubungan yang signifikan antara tingkat pendidikanorang tua dengan bentuk kekerasan pada anak.